The solution structure of a d[C(TTCG)G] DNA hairpin and comparison to the unusually stable RNA analogue. - James, J K (1993)
The solution structure of the DNA analogue of the unusually stable r[C(UUCG)G] RNA hairpin, 5'-d[GGA-C(TTCG)GTCC]-3', has been determined by NMR spectroscopy, and its structure has been compared to that of the RNA molecule. The RNA molecule is compact and rigid with a highly structured loop. However, the DNA molecule is much less structured. The DNA hairpin contains a B-form stem of four base pairs. The terminal base pair frays, and the 3'-terminal nucleotides, C11 and C12, are in equilibrium between 2'-endo and 3'-endo conformations. Unlike the RNA loop, the DNA loop contains no syn nucleotides, and there is no evidence for base-base or base-phosphate hydrogen bonding in the loop. The loop is flexible, and reveals no specific internucleotide interactions.